The Importance of Relationship development in the GCC region - Kurian, Dias Joseph; Kapasi, Anshul; Ayrancioglu, Oguz (2012)
The noun ‘Relationship’, is defined by Collins English Dictionary (2012) as 1. the state of being connected or related 2. association by blood or marriage; kinship 3. the mutual dealings, connections, or feelings that exist between two parties, countries, people, etc. a business relationship You can see from the above definition that there are several inferences that can be developed out of this single word. But is a relationship easily discernible? Are its dimensions opaque or transparent? Can it be easily contrasted simply by looking at it? Can it be evolved, grown, diminished, or separated? These are questions, if they are faced, they could make a simple word like ‘relationship’ look vague, abstract, and sometimes utterly confusing. In fact, discerning the intricate and delicate web of relationships is an art that requires not just looking at it from a single dimension but comprehending it through an experience in its entirety. Our client M/s Balfour Beatty Rail, UK (from now on as BBR) has chosen us as a three member team for our MBA company-based management project. Our aim is to analyse the importance of relationships in the Arab World, and analyse its critical dimensions. Currently, BBR’s culture, environment, organisational periphery, and business algorithms are different than what the Arab World requires as a pre-requisite for any business activity in the region. These pre-requisites are certain forms of relationships that are not easily understood in Western cultures. The region, as we have witnessed through our research, does accept Western ideas, concepts of development, and innovation but not at all at the expense of relationships (Hutchings and Weir, 2006). We felt very early in the project that these relationships, which are embedded in the socio-political and socio-cultural aspects of the region are seldom understood or even accepted by Western organisations and its people, normally resulting in bitter experiences of the region (Little, 2004). We also believe that BBR also has all the capabilities, competencies, legacy, and attributes that can help it be a winner in this region. But winning in the GCC market requires more than just competencies, abilities, or strengths (Kurian et al., 2012a). In our opinion the major ceteris paribus quotient of success within the region is about discerning and articulating the underlying relationships of the region (Hutchings and Weir, 2006), and so along with BBR’s competencies, resources, and presence the organisation needs to understand, accept, emulate, and develop viable relationships in the region. Our research identifies and analyses these elusive, opaque cultural aspects in the backdrop of evaluating the current and future rail infrastructure business development opportunities that have erupted in the region since 2006 and weaves together an argument for BBR’s immediate and long-term presence in the region along with the essential elements that should go with it.